HerArmour : Empowering Women Safety Through Technology - Kaushik, Akhil; Khanna, Satvika; Kumar, Abhishek (Indian Journal of Computer Science, 2025)
In recent years, the growing concern over women’s safety has highlighted the need for proactive and technology driven solutions. This paper presents the design and development of a compact and stylish wearable security device called HerArmour which is aimed at providing real-time protection and rapid emergency response for women. The device integrates key features such as one-touch SOS activation, GPS based location tracking, emergency alert transmission to predefined contacts, and shockwave generator. Built on an embedded microcontroller platform, the device was tested for reliability, response time, usability, and battery efficiency. The present paper demonstrates the potential of affordable and accessible technology to empower women and improve personal security in dire situations.